Media coverage of internally displaced persons in two selected newspapers in Nigeria - Eric Msughter Aondover; Abdulrahman Uba Daushe; Omotola Ogunbola; Perpetua Ogechi Aondover (Journal of Migration and Health)
The study focused on the coverage of Internally Displaced Persons (IDPs) in two selected newspapers. It aims to understand the extent and nature of the coverage of IDPs in these newspapers, taking into consideration the various reasons for displacement, such as conflicts and disasters, religious or political persecution, and economic necessity. Through an analysis of the selected newspapers, the study aims to shed light on the portrayal of IDPs, providing a comprehensive understanding of the issue and potential areas for improvement in media coverage. The variables of frequency, prominence, and direction were used to assess the coverage and reporting of IDPs by two Nigerian newspapers, Daily Trust and The Guardian from July, 2023 to December 2023. The study employed the method of content analysis, with coding sheet as an instrument of data collection. Additionally, agenda-setting was adopted in the study. The study period spanned over the population of Nigerian newspapers, while the sample size was made up of Daily Trust and The Guardian newspapers from which 126 editions was analyzed. Based on the data obtained, it is evident that the two newspapers reported the incident of internally displaced person in form of news stories. Similarly, despite the high rate of IDPs, the frequency of media coverage is still low. The selected newspapers cover internally displaced persons more in the inside page than the front and back pages. The study concluded that as the watchdog of the society, the media should put in more effort in reporting cases of internally displaced persons to the appropriate authorities so that proper actions will be taken in addressing the issue of IDPs.